Investigation of the quality of life of patients with hypertension in health centers - Farbod Ebadi Fard Azar; Mahnaz Solhi; Fakhreddin Chabaksvar (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Hypertension is one of the most critical factors for chronic diseases such as cardiovascular disease, stroke, arrhythmias, heart failure, and renal disease. The aim of this study was to evaluate the quality of life and its related factors in hypertensive patients. MATERIALS AND METHODS: This study was descriptive research. The sampling method was simple random, i.e., 137 were selected among the ten health centers of the list of the existing patients by simple random sampling. Data were collected using a questionnaire World Health Organization Quality of Life-BREF (Short Form-26). After collecting the questionnaires, the data analysis was carried out using SPSS software and using statistical methods (e.g., number, percentage, mean, standard deviation, and MANOVA tests). RESULTS: The results showed that the mean score for the physical domain (52.82), the psychological domain (50.26), the social domain (48.33), the environmental domain (46.1), and the total quality of life (49.60). Among the demographic variables, the education level variable (P =0.000), job (P = 0.013), and the duration of hypertension (P = 0.039) were significantly correlated with the quality of life of patients. The "levels of education" variables are significantly correlated with the physical domain (P = 0.000), psychological domain (P = 0.000), social domain (P = 0.000), and environmental domain (P = 0.000) of the quality of life. The "job status" variable is only significantly correlated with the social domain of the quality of life (P = 0.005). The "duration of hypertension" variable is only significantly associated with the physical domain of the quality of life (P = 0.011). CONCLUSION: The findings of the present study show that demographic variables such as educational level, occupation, and duration of hypertension have a significant relationship with the quality of life domains of hypertensive patients. It is recommended that the principled education of patients is a step toward the improvement of the quality of life of patients.